Ethyl Methane Sulfonate (EMS) Effect on Mutagenesis in Balinese Red Rice (Oryza sativa cv. Barak Cenana) - Ida Bagus Made Arta Dana; Popy Hartatie Hardjo; Maria Goretti Marianti Purwanto; Aloysia Sri Pujiyanti; Indriyani Indriyani (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2021)
Ã¢â¬ÅBarak CenanaÃ¢â¬Â is one of the local red rice (Oryza sativa) with high economic value due to its nutrient content. Some of the agronomic characters such as tall shoot, low number of tiller, and late harvesting are drawbacks to improving production. Ethyl Methyl Sulphonate (EMS) is a chemical mutagen widely used to improve rice characters by mutation breeding. The present research aims to investigate the EMS concentration suitable to induce mutation in Barak Cenana and observe the mutagenesis effect of EMS on some agronomic characters of Barak Cenana. For those purposes, mature seeds of Barak Cenana were treated with various concentrations of EMS (0.25, 0.5, 0.75, 1.0, and 1.1 %) for 24 hours. Seed germination, plant growth, some agronomic character related to productivity were compared to untreated rice. EMS reduced and delayed seed germination and inhibit shoot and root growth in early vegetative stage. The ability of EMS to reduce and delay seed germination and inhibit shoot and root growth were doses dependent. EMS concentration of more than 1.0% was lethal for Barak cenana and EMS concentration at 0.75% was able to reduce rice productivity by increasing seed sterility. EMS concentrations between 0.25 and 0.5% with 24 h of soaking are suitable for inducing mutagenesis in Barak Cenana. Additionally, some mutants with distinct morphology such as sterile plant, semi-dwarf, high tillering capacity, and high chlorophyll contents were produced in this research.